SPECIFIC ASPECTS OF EVIDENCE GATHERING IN ASSET IMPAIRMENT AUDIT PROCESSES - Sayfullayev Mekhroj Sayfullayevich,; Khotamov Alisher Khotamjon o’gli, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article examines the specific aspects of evidence gathering in asset impairment audit processes, and provides suggestions and recommendations on them.